Um modelo multivariado para predição de taxas e proporções dependentes - (:unkn) unknown (Universidade Federal do Amazonas, 2018)
Relative humidity interferes in many aspects in the life of the human being, and due to the many consequences that a low or a high percentage can entail, the control of its level is of paramount importance. Thus, the modeling of extreme situations of this variable can aid in the planning of human activities that are susceptible to their harmful effects, such as public health. The main interest is to predict, based on probability density functions applied to observed data, the values that may occur in a certain locality. The Generalized Distribution of Extreme Values has been widely used for this purpose and research using Time Series analysis of meteorological and climatic data. In this work, a statistical model is proposed for prediction of rates and temporal proportions and/or spatially dependents. The model was constructed by marginalizing the Kumaraswamy G-exponentialised distribution conditioned to a random field with positive alpha-stable distribution. Some properties of this model were presented, procedures for estimation and inference were discussed and an MCEM algorithm was developed to estimate the parameters. As a particular case, the model was used for spatial prediction of relative humidity in weather stations at Amazonas state, Brazil.
Keywords: Distribuição Kumaraswamy; Distribuição alfa-estável; Algoritmo MCEM; Umidade relativa do ar; Kumaraswamy distribution; Alpha-stable distribution; MCEM algorithm; Relative humidity; CIÊNCIAS EXATAS E DA TERRA: MATEMÁTICA